Measurement of the WZ production cross section in pp collisions at root s=7 and 8 TeV and search for anomalous triple gauge couplings at root s=8 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Ero, J.; Flechl, M.; Friedl, M.; et al. (Springer, 2017)
The WZ production cross section is measured by the CMS experiment at the CERN LHC in proton proton collision data samples corresponding to integrated luminosities of 4.9 fb(-1) collected at root s = 7 TeV, and 19.6fb(-1) at root s = 8 TeV. The measurements are performed using the fully-leptonic WZ decay modes with electrons and muons in the final state. The measured cross sections for 71 < m(Z) < 111 GeV are sigma (pp -> WZ; root s = 7 TeV) = 20.14 +/- 1.32 (stat)+/- 0.38 (theo)+/- 1.06 (exp)+/- 0.44 (lumi) pb and sigma (pp -> WZ; root s = 8 TeV) = 24.09 +/- 0.87 (stat) 0.80 (theo) +/- 1.40 (exp) +/- 0.63 (lumi) pb. Differential cross sections with respect to the Z boson p(T), the leading jet p(T), and the number of jets are obtained using the root s = 8 TeV data. The results are consistent with standard model predictions and constraints on anomalous triple gauge couplings are obtained.